Susceptibility-Weighted Imaging in the Diagnosis of Early Basal Ganglia Germinoma - Lou, X. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Germinomas originating from the basal ganglia (BG) are rare. Early diagnosis is important for favorable prognosis, but it is difficult due to the slow clinical course and subtle changes on neuroimaging. The purpose of this study was to evaluate the usefulness of susceptibility-weighted imaging (SWI) in the diagnosis of early BG germinoma. MATERIALS AND METHODS: From 2006 to 2008, 6 BG germinomas were diagnosed in children at our institution by pathology. Conventional MR imaging and SWI were available in all cases. Clinical, neuroradiologic, and follow-up features were retrospectively studied. RESULTS: Three cases were classified as early BG germinomas. Conventional MR imaging demonstrated that the tumor size was <10 mm in the largest diameter. The tumors were invisible or showed slight hyperintensity on T1-weighted images (T1WI) and patchy slight hyperintensity on T2-weighted images (T2WI) without mass effect or enhancement. On SWI, the tumors appeared as obvious hypointensity in the globus pallidus and putamen, and the size was larger than that on conventional T1WI and T2WI. The other 3 cases with tumor size >10 mm in largest diameter were classified as late BG germinomas, with tumor necrosis, fluid-fluid levels, and perifocal edema, including 1 case with subependymal spread. On SWI, only the solid portion of the tumors showed hypointensity. No recurrence was noted on follow-up. CONCLUSIONS: SWI appears to be more sensitive in detecting early BG germinomas than conventional MR imaging. This capability may prove to be useful in future attempts to characterize early BG germinomas.